Deformation Pattern of Expanded Polystyrene (EPS) and Palm Oil Fuel Ash (POFA) Concrete Subjected to Experimental Pullout Test - Su, Kah Won; Mohamad Hairi Osman (Progress in Engineering Application and Technology, 2024)
In the constrcution industry, concrete is widely used in various situation, yet the conventional concrete often grapples with density limitations, bonding strength and environmetal challenges. Seeking innovative solutions, this study navigates the integration of Palm Oil Fuel Ash (POFA) and Expanded Polystyrene (EPS) into concrete matrices, aiming to not only address these drawbacks but also elevate its performance. This research aims to meticulously investigate the performances of concrete containing POFA and EPS by conducting experimental pullout test. The focus is on uncovering the maximum pullout capacity and deformation patterns of the concrete specimen in detail. Employing established British Design of Experiments (DoE) techniques and adhering to concrete M20 grade standards, this study explores different replacement ratios of EPS and POFA within concrete compositions, accompanied by comprehensive assessments encompassing slump tests, density analyses, pullout capacity and deformation pattern evaluations. The combination of POFA, renowned for its pozolannic properties, and EPS, recognized for its lightweight properties, offers a promising avenue for revolutionizing concrete’s mechanical behavior and structural integrity.Palm Oil Fuel Ash (POFA), Expanded Polystyrene (EPS), deformation pattern, pullout test